Antibiotics and Resistance: Past, Present, and Future - Hackenberger, Dirk (My University, 2025)
Antibiotics are the foundation of health systems worldwide. Consequently, antimicrobial resistance is an urgent threat to global health, driven by complex evolutionary, ecological, and socioeconomic forces. This thesis explores aspects of the history, present state, and possible future of antibiotics and their associated resistance. By better understanding these facets, we might better combat the developing crisis. First, I demonstrate how the prolific military use of sulfonamides during World War 2 likely selected for a chance association between class I integrons and sul1, a sulfonamide resistance gene. This selection pressure is potentially responsible for the worldwide seeding of class I integrons, positioning them ideally to adopt new antibiotic resistance genes that would be selected for by new antibiotics released after World War 2. Understanding this foundational event is critical to contextualize the development of antimicrobial resistance in Gram-negative pathogens. Second, I developed a cost-effective strategy to modernize resistome characterization in metagenomic samples. By using hybridization-based enrichment with next-generation sequencing and in-house synthesized reagents, I have cut the typical cost of this protocol by over ten-fold, opening its use to various stakeholders. Finally, I explore the evolutionary history of a recently discovered biosynthetic gene supercluster that encodes proteins to construct four molecules, all of which target biotin biosynthesis. By leveraging insights from this supercluster, I have found three more potential superclusters, all of which can likely be captured and expressed using novel heterologous capture protocols. This work is a step towards the future of natural product drug discovery, where bioinformatic methods may find promising lead compounds. Together, these studies underscore that antimicrobials and their associated resistance exist in a space shaped by evolutionary, ecological and socioeconomic factors. They expand our knowledge of the underappreciated historical drivers of antimicrobial resistance while highlighting the need and offering solutions for proactive monitoring and innovative discovery approaches.
Keywords: Antimicrobial Resistance; Antibiotics